Multi-walled carbon nanotubes doped Poly(Methyl MethAcrylate) microfiber for relative humidity sensing - Isa, Naimah Mat; Irawati, Ninik; Harun, Sulaiman Wadi; Ahmad, Fauzan; Rahman, Husna Abdul; Yusoff, Mohd Hanapiah Mohd (Elsevier, 2018)
Multi-walled carbon nanotubes (MWCNTs) doped Poly(Methyl MethAcrylate) (PMMA) microfiber was proposed and demonstrated for relative humidity sensing. It was prepared through a direct drawing technique to achieve a diameter of 5 μm and a length of 5 mm. As the relative humidity increases from 45% to 80%, the output power of the sensor decreases linearly with a sensitivity of 0.3341 dBm/% and a resolution of 1.649%. The result signifies that PMMA doped with MWCNTs exhibits better sensitivity and higher resolution compared to the un-doped PMMA microfiber sensor. In addition, the sensor exhibits high reliability as well good repeatability.